CULTURAL DEVELOPMENT AND FAMILY OF TURKISH PEOPLE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article describes the Uzbek family, its specific features and important changes taking place in its life in the context of globalization, the issues of the coherence of these trends with changes in the life of families in Turkic-speaking countries.